Implementation of Islamic Educational Values According to Q.S Ash-Shaffat Verse 102 in Forming Students' Character and Morals - Rahmat Azid Muslim; Akil; Agus Susanto (Institut Agama Islam Negeri (IAIN) Curup, 2025)
Islam as a religion rahmatan lil 'alamin makes the Qur'an the most rule in considering, carrying on, and carrying on, counting in perspectives of instruction and character building. Islamic instruction does not as it were center on the exchange of knowledge, but moreover points to make character and respectable ethics in understanding with the lessons of the Qur'an. One of the verses that contains the values ​​of character instruction is Surah Ash-Shaffat verse 102, which appears the model behavior of the Prophet Ibrahim and the Prophet Ismail in carrying out Allah's commands with truthfulness, acquiescence, and tolerance. This ponder points to investigate the execution of Islamic instructive values ​​in Surah Ash-Shaffat verse 102 within the arrangement of character and morals of understudies at SMPIT INSAN KAMIL, Bekasi Rule. The strategy utilized could be a subjective approach with perception, meet, and documentation strategies. The comes about of the ponder demonstrate that the usage of Islamic instructive values ​​in Q.S. Ash-Shaffat verse 102 at SMPIT Insan Kamil, Bekasi Rule has succeeded in shaping the character and ethics of understudies essentially. Values ​​such as freedom, obligation, pondering, acquiescence, and tolerance are coordinates in a arranged way through learning, devout exercises, and school culture. As a result, understudies appear positive improvement both profoundly and socially, reflecting people with character and noble morals concurring to the illustration of Prophet Ibrahim (AS) and Prophet Ismail (AS).